How Do Chinese International Students View Seeking Mental Health Services? - Chen, Huan; Akpanudo, Usenime; Hasler, Erin (Journal of International Students, 2020)
This study explored how Chinese international students view seeking mental health services. One hundred and ten Chinese international students responded to the Attitude Toward Seeking Professional Psychological Help Scale–Short Form (ATSPPH-SF) and a demographic questionnaire. Results of our data analysis revealed no significant main effects of the demographic factors (gender, length of stay in the United States, and awareness of on-campus counseling services) on attitudes toward seeking mental health services. However, awareness of on-campus counseling services was found to be a mediating factor in the relationship between gender and students’ mental health help-seeking attitudes. Based on the findings, we make recommendations on how student affairs professionals can better serve the mental health needs of Chinese and other international students.